PANDEMIZATION AND THE NEW NORMAL - Lukić, Aleksandar (Political Review, 2023)
The paper investigates the phenomenon of a declared pandemic and the processes that take place within such a situation. It's about processes in education, culture, economy and social life in general. Those processes could not have happened if the pandemic had not been declared. It can be said that we are living in a turning point that should establish a new state of affairs in public and private life. That new state of affairs actually implies a new paradigm that represents a kind of refeudalization in terms of various parameters related to significant denial of various rights and freedoms. The new paradigm includes a significant degree of control, ie. various forms of supervision and forced medical treatments. The new state of affairs has its own slogans such as “social distancing”, ”new normal“, “digitalization”, etc. Those slogans are contrasted with the slogans of freedom, equality and fraternity that marked the creation of civil society during the French Revolution.The declaration of a pandemic enabled the introduction of restrictive measures that go beyond medicine and primarily relate to basic human rights and freedoms. In this way, from the sphere of medicine it entered to the sphere of philosophy, sociology, politics and other areas of human social practice. Propaganda has produced a situation in which it has made fear a desirable state of affairs. Those who were not afraid, as a rule, were declared non-solidarity and irresponsible persons who endanger other people, the health system, the functioning of the state, etc. People agreed to the measures either out of primal existential fear or out of fear of punishment if they do not respect the measures. Deconstruction of the so-called old normal would also represent the deconstruction of the existing civil society and the establishment of some kind of new totalitarianism.The articles of recognized scientists, such as Kary Mullis, Luc Montagnier, John Ioannidis, etc., if they did not fit into the given matrix, were either ignored or declared unscientific.It could be argued that the declared pandemic was primarily a political project. Its factual ending also testifies to this. Pandemization entered a stand-by state when the Russian special military operation on the territory of Ukraine began in February 2022.
Keywords: pandemic; pandemization; new normal; freedom; social distancing; great reset; new paradigm